APLIKASI KEANEKARAGAMAN BUDAYA DI INDONESIA BERBASIS ANDROID (Information Technology and Telematics, 2014)
Abstract - Indonesia is one country that has such a wide variety of ethnic richness of culture, customs, clothing, weapons and so on. This is because Indonesia has a culture which is the culture Javanese, Batak, Sundanese, Malay and many various cultures in Indonesia. in the study of culture is not easy to learn one must go where the place of origin to find the original culture and appreciate the culture throughout the country. Where many incoming foreign culture in the community so that children or adolescents preferred the foreign culture of the culture in Indonesia. Here the authors attempt was made to apply an information search tool in order to help facilitate the users to get the custom house, weapons, clothing, musical instruments, traditional house, dance, tradition and complete description along in Indonesia. The final result in the development of this system, the author uses the Prototype models and using the Java programming language and a SQLite database table containing 7 classes in every province. Which will be installed on the mobile and Making an application program using the Eclipse application. Keywords: Diversity, Culture of Indonesia, Android